2018
DOI: 10.1111/apt.15005
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with network meta‐analysis: the impact of medical interventions for moderate‐to‐severe ulcerative colitis on health‐related quality of life

Abstract: Summary Background Patient‐reported outcomes are important in the assessment of efficacy of intervention for ulcerative colitis (UC). Aim To compare the impact of interventions for moderate‐to‐severe UC on health‐related quality of life (HRQL). Methods We searched Medline, Embase, CENTRAL and grey literature sources through October 2017. We included randomised controlled trials (RCTs) that compared infliximab, adalimumab, golimumab, vedolizumab or tofacitinib to each other or placebo. Outcomes included the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 38 publications
0
38
0
7
Order By: Relevance
“…3,4 In parallel, biologic therapies, particularly those that target tumour necrosis factor-alpha (TNF-α) have been increasingly used for the treatment of IBD due to their superior efficacy to older conventional medical therapies including 5-aminosalicylic acid (5-ASA), corticosteroids, thiopurines and methotrexate. 5,6 Although these treatments have been shown to improve the quality of life and work-related productivity, 7 it is expected that their broader use is also associated with rise in direct health cost expenditures. Therefore, there is increasingly a need for comprehensive assessment of societal cost of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In parallel, biologic therapies, particularly those that target tumour necrosis factor-alpha (TNF-α) have been increasingly used for the treatment of IBD due to their superior efficacy to older conventional medical therapies including 5-aminosalicylic acid (5-ASA), corticosteroids, thiopurines and methotrexate. 5,6 Although these treatments have been shown to improve the quality of life and work-related productivity, 7 it is expected that their broader use is also associated with rise in direct health cost expenditures. Therefore, there is increasingly a need for comprehensive assessment of societal cost of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable attention is currently being paid to the clinical development of JAK inhibitors for IBD. Two previous network meta‐analyses have demonstrated that tofacitinib, an oral JAK1/3 inhibitor, is effective for achieving clinical, endoscopic and quality of life outcomes compared to placebo in patients with UC . However, negative trial results from two phase II studies of tofacitinib in CD and one trial of peficitinib in UC, as well as an increased risk of infections, particularly of herpes zoster, has raised questions regarding the risk‐benefit profiles of this class of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…As for the inclusion of three RCTs in the present pooled analysis, it is considered adequate in terms of methodology [ 37 , 38 ], with many recent meta-analyses published in high-impact journals synthetizing data from three RCTs [ 42 , 43 ]. While some might argue that a systematic review alone might be more appropriate, it is characteristic, that the median number of studies included in meta-analyses of cardiovascular events published in the Cochrane Reviews is reported to be three [ 44 ], whereas even in UC research, recent meta-analyses have pooled three to four RCTs [ 45 ]. Although undoubtedly more is better meta-analysis-wise, with three pooled RCTs being considered adequate, researchers should focus more on the methodological quality [ 46 ], rather than what is individually perceived as an adequate sample size.…”
Section: Discussionmentioning
confidence: 99%